Heterogeneity of Bank Risk Weights in the EU : Evidence by Asset Class and Country of Counterparty Exposure - Turk-Ariss, Rima (IMF Working Papers; Working Paper ;, 2017)
Concerns about excessive variability in bank risk weights have prompted their review by regulators. This paper provides prima facie evidence on the extent of risk weight heterogeneity across broad asset classes and by country of counterparty for major banks in the European Union using internal models. It also finds that corporate risk weights are sensitive to the riskiness of an average representative firm, but not to a market indicator of a firm's probablity of default. Under plausible yet severe hypothetical scenarios for harmonized risk weights, counterfactual capital ratios would decline significantly for some banks, but they would not experience a shortfall relative to Basel III's minimum requirements. This, however, does not preclude falling short of meeting additional national supervisory capital requirements.